Inflation and Income Distribution : Further Evidenceon Empirical Links - Bulir, Ales (IMF Working Papers; Working Paper ;, 1995)
This paper examines the effects of inflation and associated financial instability on income distribution. Using both pooled cross country and single country time series models, the level of inflation, inflation variability, and the variability of the nominal exchange rate are shown to impact negatively on overall income equality. Looking at disaggregate measures of income distribution, the issue as to whether inflation is a progressive or regressive tax is found to be negatively correlated with the level of development and the sophistication of the financial structure. The paper argues that these results point towards financial variables as a partial way of rectifying the generally poor explanatory power of both cross-country and time series models of income distribution.